Technology and healthcare into the future - N.H. Edwards (Journal of Innovation in Health Informatics, 1999)
Information technology has been developing rapidly over the last two decades, and has already become essential to many aspects of health care delivery. Furthermore, the current NHS Information Strategy1 shows commitment at the highest level for revolutionising the delivery of health with the adoption of the latest information technology. This paper reviews a number of areas where information technology is being applied in new ways for health care, and explores some new and emerging technologies that may have an impact on health care provision in the future.